Vrednotenje uspešnosti jezikovnih politik in jezikovnih pobud za rabo valižanskega jezika v Walesu - Gale, Špela (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2016)
Editing of the minority protection area in Europe often evolved in an uncertain historical context. Strong regional movements, which emphasized the value of regional, linguistic and social particularities of the European peripheral communities, marked the middle of the 60s of the last century. Wales represents the officially bilingual region, which is characterized by a monolingual majority and bilingual minority. The Welsh language represents a rich laboratory of innovative best practices and strategically premeditated language initiatives in the areas of planning of the use of Welsh language, and the strategically thoughtful language initiatives, designed on comprehensive social networks (networking). Based on an analysis of primary and secondary data sources as well as with an additional field work, we have tried to summarize the evaluation of the performance that shapes language policies and selected language initiatives, and find among them examples that were innovative and efficient in terms of the language use prevalence changes.
Keywords: Wales; manjšine; jezikovna zakonodaja; jezikovna politika; promocija manjšinskega jezika; družbena raba jezika; valižanski jezik